Exposing Animals to Oxidant Gases: Nose Only vs. Whole Body - Cheng, Yung Sung (American Thoracic Society, 2010)
Inhalation experiments using laboratory animals are performed under controlled conditions to assess the toxicity of and to investigate interventional strategies to ameliorate injury resulting from oxidant gas exposures. A variety of dynamic inhalation exposure systems that use whole-body or nose-only exposure chambers have been developed for rodents. In a whole-body exposure chamber, the animals are immersed in the test atmosphere, whereas in nose-only or head-only exposure systems, exposures are localized primarily to the head and/or nasal regions. There are advantages and disadvantages with both types of exposure approaches. Considerations such as animal number, exposure duration, end points of study, and availability of test material should influence the selection of a particular exposure system.